A single‐nucleotide polymorphism of miR‐196a‐2 and vitiligo: an association study and functional analysis in a Han Chinese population. (25th March 2013) - Huang, Ye; Yi, Xiuli; Jian, Zhe; Wei, Chao; Li, Shuli; Cai, Chuan; Zhang, Ping; Li, Kai; Guo, Sen; Liu, Ling; Shi, Qiong; Gao, Tianwen; et al.
Summary: Recent evidence indicates that oxidative stress and genetic factors play an important role in the pathogenesis of vitiligo. SNPs in miRNAs involved in oxidative stress could potentially influence the development of vitiligo. In this case–control study, we investigated the association of a functional SNP of rs11614913 in miR‐196a‐2 with risk of vitiligo. A significantly lower risk of vitiligo was associated with the rs11614913 miR‐196a‐2 CC genotype (adjusted OR, 0.77; CI, 0.60–0.98). In addition, TYRP1 gene expression was considerably down‐regulated by the rs11614913 C allele in miR‐196a‐2, which lowered the levels of intracellular reactive oxygen species (ROS) and reduced the proportion of early apoptosis in human melanocytes in response to H2 O2 treatment. Our data suggest that the rs11614913 C allele in miR‐196a‐2 confers potential protection against oxidative effects on human melanocytes through the modulation of the target gene, TYRP1, which may account for the decreased risk of vitiligo in this study population.